CONTRACEPTIVE EFFECT OF NEEM SEED OIL AND ITS ACTIVE FRACTIONS ON FEMALE ALBINO RABBITS - Vyas, Vijeyata; Purohit, Ashok (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In the present investigation, contraceptive efficacy of neem seed oil and its fractions have been examined in female albino rabbits to find out their contraceptive potential. Methods: The experimental protocol was designed for intact control, Neem seed oil alone and its six active fractions in eight groups for 30 days. The estimation of serum biochemistry, histometry of reproductive organs, and hematological parameters were done. Results: Oral administration of Neem seed oil alone and its Fraction IV and V causes significant reduction in weight of ovary and uterus which reflects antiestrogenic function of plant material. Significant increase in serum cholesterol and phospholipid in Neem seed oil alone and its Fraction IV and V-treated groups reflects that they may affect the intraovarian estrogen level either by inhibiting the ovarian cell function or by inhibiting follicle-stimulating hormone and luteinizing hormone secretion through hypothalamus-hypophysis axis and impaired estrogen synthesis. Conclusion: From the ongoing work, it can be concluded that Neem seed oil alone and its Fraction IV and V cause functional sterility in female albino rabbits without causing any side effect on general metabolism.